(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
In the classical literature of the East there are traditional images, which are repeated in stories, legends, epics and in general creative works and have become known and popular to everyone. One of such images is the image of the wise man. In the literature and historical books of the Near and Middle East, he is called the wise man, the wise man.